Systemic Free Heme Increases the Risk for Acute Kidney Injury (AKI) after Solid Organ Transplantation. (July 2018) - Doricic, Julian; Vijayan, Vijith; Leffler, Andreas; Richter, Nicolas; Granas, Gerrit; Warnecke, Gregor; Haller, Hermann; Immenschuh, Stephan; Gueler, Faikah
Abstract : Background: Acute kidney injury (AKI) is a frequent complication after solid organ transplantation. Especially, lung-, heart- and liver transplantation are associated with substantial blood loss and the need of blood replacement. Packed red blood cell (pRBC) are beneficial and in many cases lifesaving. However, ageing of pRBC can cause release of toxic extracellular hemoglobin (hb) and heme which contribute to acute organ dysfunction. In this study, systemic heme release after orthotopic heart transplantation was compared to kidney transplantation in patients. Methods: Patients undergoing heart transplantation (htx, n=10) or kidney transplantation (ktx, n=7) at the Hannover Medical School were enrolled in a prospective clinical study and blood sampling was done prior to surgery, during surgery, at 6 and 24h, 1 and 7 days after surgery. Free heme quantification was based on measuring peroxidase enzyme activity and was compared to clinical outcome parameters such as s-creatinine, LDH. Results: The patients undergoing htx developed systemic increase of free heme within 30min after surgery from baseline levels (9 fmol/nl) up to 3760 – 17255 fmol/nl after surgery. LDH increase ranged from 278 up to 834 – 4539 U/L after surgery. AKI rate was 60% and most prominent in patients with complicated surgeries and large amount of pRBC transfusion (6 to 24 pRBC packages were needed during surgery). In contrast, patients undergoing ktx had only minor systemic heme release and did not need any pRBC transfusion. Discussion: pRBC are stored up to 42 days in Germany and during that time ageing occurs with release of free hemoglobin, free heme and iron. All of them are vasoactive and pro-inflammatory mediators. The current study indicates that in the context of htx excessive systemic heme release is measurable and correlates with LDH increase and acute kidney injury. These patients need up th 24 pRBC transfusions. In comparison after ktx only minor increase of free heme was measured even though cold ischemia time of the allografts were up to 20 hours. Free heme is vasoactive and can cause microcirculation disturbances and is a strong inductor of complement activation and inflammation. Conclusion: Transfusion of pRBC in the context of major surgery and htx can lead to increased systemic heme and might be a risk factor for AKI. Strategies to measure hemoglobin degradation in pRBC during storage and prior to transfusion could be of relevance to develop strategies to enhance patient safety.